2015
DOI: 10.1155/2015/792780
|View full text |Cite
|
Sign up to set email alerts
|

A Major Complication in Micropercutaneous Nephrolithotomy: Upper Calyceal Perforation with Extrarenal Migration of Stone Fragments due to Increased Intrarenal Pelvic Pressure

Abstract: Micropercutaneous nephrolithotomy is a safe and efficient technique for appropriate sized stones. It is performed through a 4.85 Fr all-seeing needle and stones are fragmented into dust, without the need for tract dilatation, unlike other percutaneous nephrolithotomy types. Even though micropercutaneous nephrolithotomy has many advantages, increase in intrapelvic pressure during surgery may cause rare but serious complications. Herein we report a case of micropercutaneous nephrolithotomy in a 20-year-old woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…For instance, since the operation of PCNL requires continuous washing to maintain a clear vision field, increased incidence of septicemia could be induced [13]. Furthermore, a certain degree of bleeding is unavoidable with PCNL since kidney is a vascular organ [14]. Unlike SPCNL, MPCNL is equipped with a smaller access tract and does not require serial dilatation, and patients receiving MPCNL may experience smaller Hb drop, decreased trauma, and reduced bleeding amount [15].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, since the operation of PCNL requires continuous washing to maintain a clear vision field, increased incidence of septicemia could be induced [13]. Furthermore, a certain degree of bleeding is unavoidable with PCNL since kidney is a vascular organ [14]. Unlike SPCNL, MPCNL is equipped with a smaller access tract and does not require serial dilatation, and patients receiving MPCNL may experience smaller Hb drop, decreased trauma, and reduced bleeding amount [15].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 A técnica que descrevemos é uma variação da original e faz uso da colocação de uma bainha ureteral para permitir a redução da pressão intra-renal bem como a contínua evacuação dos fragmentos no decorrer do procedimento.…”
Section: 13unclassified
“…Thus, less invasive and more refined instruments have been developed, such as those used during mini-PCNL and ultramini-PCNL. [2][3][4][5][6] Bader et al 3 established percutaneous renal tracts using a 16-gauge optical puncture system in 2011. Desai et al 7 first reported on the puncture and disintegration of urinary stones in a single step without tract dilation and named this innovative PCNL "microperc. "…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, microperc went on to be used to treat moderate-size renal stones in an effort to reduce tract size and tract-related complications. 4,5,[8][9][10][11][12] Advantages of the single-step procedure without tract dilation are minimal tract bleeding, high likelihood of terminating the procedure without tubes, and reduced postoperative pain and hospitalization. 5,8,13 Nevertheless, microperc has drawbacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation